1999
DOI: 10.1177/014556139907800813
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Comorbidity and Age on Survival with Laryngeal Cancer

Abstract: Previous studies ha ve evaluated the effe cts of como rbidity on survival in patient s with cance r. We app lied the Charlson comorbidity index (CCl) to a coho rt ofpatients with laryngeal cance r to validate its use and to assess the prognosti c impact of age . Our study p opulation consisted of 152 patients with laryngeal cance r who we re see n ove r a JO-yearperiod. Patient s we re ass igned CCl sco res and were catego rized into low-and high -grade como rbidity groups fo r comparison. Age adjustm ents we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 12 publications
3
43
1
1
Order By: Relevance
“…But, in contrast to our results, incorporating age as an additional comorbid condition did not improve the prognostic ability of the CCI. (6) The current study, however, examined the prognostic impact of age and comorbidities in a uniform cohort of T3–T4 laryngeal SCC. We demonstrated, matching with data reported in previous studies, that both age and comorbidities are strong prognostic factors in locally advanced larynx cancer independent of treatment modality due to the high impact of both factors on non-cancer related competing mortality risk.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…But, in contrast to our results, incorporating age as an additional comorbid condition did not improve the prognostic ability of the CCI. (6) The current study, however, examined the prognostic impact of age and comorbidities in a uniform cohort of T3–T4 laryngeal SCC. We demonstrated, matching with data reported in previous studies, that both age and comorbidities are strong prognostic factors in locally advanced larynx cancer independent of treatment modality due to the high impact of both factors on non-cancer related competing mortality risk.…”
Section: Discussionmentioning
confidence: 98%
“…These patients are at a greater risk for cardiovascular and respiratory illnesses in addition to the development of squamous cell carcinoma (SCC) in the aerodigestive tract. (16) Up to 65% of patients with head and neck cancer are afflicted with clinically relevant pretreatment comorbidities. (3, 5, 7, 8) …”
Section: Introductionmentioning
confidence: 99%
“…In addition, severe comorbidity (e.g. cardiovascular disease) seems to be a predictor for shorter survival times of laryngeal cancer patients [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…There was no difference between indexes in the survival analysis. Sabin et al 17 reported the survival analysis for a series of 152 patients with laryngeal cancer and found the Charlson Index to be a predictor of survival using univariate, Kaplan‐Meier, and Cox regression analysis. Piccirillo has reported the score distributions and 2‐year survival analysis using a modification of the KFC 18 for a series of 341 patients.…”
Section: Introductionmentioning
confidence: 99%